Exploring clinical supervision to facilitate the creative process of supervision - Zainal Abiddin, Norhasni (The Journal of International Social Research, 2008)
Good supervisory practices help students fulfill their potential and contribute to the university’s research profile. This article reviews the literature on clinical supervision. It describes best practices in clinical supervision, and set out the rights and responsibilities of both students and their supervisors. It is intended to provide some useful guidelines for students and supervisors (not only for clinical students) to encourage the development of relationship in the first place. Therefore, a review of literature concerning clinical supervision is hoped to assist all participants in the supervisory process to articulate their expectations clearly, and thereby to reduce potential problems and to facilitate the creative process of supervision.